Ginger the stray kitten. - Webb, Holly; Williams, Sophy, illus (New York : Scholastic, 2009)
Rosie loves visiting the stray cats that live on the farm near her grandmother's house and her favorite is a very shy little kitten she calls Ginger. When the farm is sold to developers and the builders start to work, the other cats disappear and the little kitten is alone and terrified.
Keywords: Cats -- Fiction; Lost and found possessions -- Fiction; Fear -- Fiction